Epstein and iron loss test for Incoming Quality Assurance (IQA) - Mastika, Abdullah; Ismail, Daut, Prof. Dr.; Yanawati, Yahya; Nor Shafiqin, Shariffuddin; Pungut, Ibrahim (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.